2019
DOI: 10.1186/s12887-019-1748-4
|View full text |Cite
|
Sign up to set email alerts
|

Identifying medication errors in neonatal intensive care units: a two-center study

Abstract: BackgroundThis study aimed to assess the types and frequency of medication errors in our NICUs (neonatal intensive care units).MethodsThis descriptive cross-sectional study was conducted on two neonatal intensive care units of two hospitals over 3 months. Demographic information, drug information and total number of prescriptions for each neonate were extracted from medical records and assessed.ResultsA total of 688 prescriptions for 44 types of drugs were checked for the assessment of medical records of 155 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 18 publications
3
24
1
2
Order By: Relevance
“…One study (Vogus & Sutcliffe, 2007) included in this review indicates that leadership styles are associated with medication errors. Medication errors are a key outcome measure because they occur commonly in ICUs (Eslami, Aletayeb, Aletayeb, Kouti, & Hardani, 2019). It has also been established that fairness and integrity are important for discerning patterns in the occurrence of medication errors (Vogus & Sutcliffe, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…One study (Vogus & Sutcliffe, 2007) included in this review indicates that leadership styles are associated with medication errors. Medication errors are a key outcome measure because they occur commonly in ICUs (Eslami, Aletayeb, Aletayeb, Kouti, & Hardani, 2019). It has also been established that fairness and integrity are important for discerning patterns in the occurrence of medication errors (Vogus & Sutcliffe, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…(17) Dentre os erros na terapia medicamentosa, a dosagem incorreta prescrita por médico (28%) e a não administração de medicamento pela(o) enfermeira(o) (29%) foram as etapas citadas como erro mais frequente em unidades de terapia intensiva neonatal. (18) Em estudo realizado em um hospital universitário francês e em uma unidade de terapia intensiva nos EUA, identificou-se que os erros de prescrição de medicamentos, cometidos por médicos, estão entre os que mais ocorrem nos serviços de saúde e são considerados graves. (19,20) De modo geral, as pesquisas sobre erro no trabalho em saúde ocorreram em hospitais.…”
Section: Discussionunclassified
“…Quanto aos elementos do contexto para a ocorrência do erro, destaca-se a inexperiência da equipe de saúde, registro ilegível de prescrições, uso de abreviaturas, tempo de formação profissional inferior a dois anos, déficit no conhecimento, estresse, distração e profissionais mais jovens, sendo estes fatores relativos a características individuais dos profissionais. (18,(25)(26)(27)(28)(29) Já em outros estudos, (30)(31)(32)(33) revelou-se a precarização do trabalho. A precarização do trabalho é um sistema político que visa à dominação e à disseminação do medo, criando um contexto de insegurança permanente no trabalhador, submetendo-o à exploração.…”
Section: Discussionunclassified
“…Nichter et al observed an incidence of medication errors in pediatric intensive care units ranging between 22 and 59 errors per 1,000 doses, seven times more frequently than other pediatric inpatient units (16). Furthermore, the reported risk of medication errors in neonatal wards is eight times higher than that of adults' ones (17,18). An incidence ranging between 13 and 91 medication errors per 100 admissions in the Neonatal Intensive Care Unit (NICU) has been estimated with rates of occurrence considerably higher in preterm neonates (75.4 vs. 24.6%) (19).…”
Section: Epidemiology Inpatient Settingmentioning
confidence: 99%